Impacts of heat stress on global cattle production during the 21st century: a modelling study. Issue 3 (March 2022) - Thornton, Philip; Nelson, Gerald; Mayberry, Dianne; Herrero, Mario
Summary: Background: Heat stress in animals is one of the major climate change impacts on domesticated livestock raised in both intensive and extensive production systems. At temperatures higher than an animal's thermoneutral zone, heat stress can affect liveweight gain, milk yield, and fertility. Animal welfare may also be negatively affected by heat stress even in the absence of effects on productivity, at least in the short term. Methods: We estimated the comparative statics change in the value of cattle milk and meat production from heat stress-induced losses at the global level, using climate scenario outputs for the middle (2045) and end of the century (2085). The loss estimates are based on bioenergetic equations that relate changes in dry matter intake (DMI) to both cold and hot, humid weather. DMI changes were estimated using CMIP6 climate data and linked to a global dataset containing information on livestock production systems, animal numbers, and region-specific and system-specific animal diets. Changes in DMI were converted to changes in milk and meat production and valued using early 20th century world prices (ie, constant 2005 US dollars). Findings: For a high greenhouse-gas emission scenario (SSP5-8.5), production losses from heat stress were estimated to amount to 39·94 billion (95% CI 34·39–45·49 billion) per year by the end of the century, or 9·8% of the value of production of meat and milk from cattle in 2005. For a low emission scenario (SSP1-2.6), the value of production losses was 14·89 billion (12·62–16·95 billion) per year, or 3·7% of 2005 value. In both scenarios, losses in most tropical regions were projected to be far greater than they were in temperate regions. Interpretation: Our results highlight the potential magnitude and extent of the adaptation efforts that will be necessary to combat the effects of increasing heat stress on cattle production during this century if food security challenges are to be minimised. Adaptations include switching to more heat-tolerant breeds and provision of shade, ventilation, and cooling systems. Funding: CGIAR Trust Fund and bilateral donors.